2022
DOI: 10.3390/ijerph192113943
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Training Focused on Psychological Flexibility for Family Members of Children with Intellectual Disabilities

Abstract: The objective of the study was to analyse the effect of a psychological flexibility intervention programme based on Acceptance and Commitment Therapy (ACT) on 36 family members of children with intellectual disabilities. The 6-PAQ (parental psychological flexibility), PSS-14 (perceived stress), GHQ-12 (psychological health), and WBSI (suppression of unwanted thoughts) were used as measurement instruments before the programme (pre), after (post), and at follow-up (after two months). Possible change in family in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…We hypothesise that this type of effect may be more visible in the long term. Although we obtained similar results (included in the general health variable) in the clinical trial previously conducted by our team, it lacked a control group [23]. This study confirmed the efficacy of the intervention, since the differences between the two groups are very notable, thus providing evidence that the changes are not due to the mere passage of time or the fact that the patients are being evaluated and know that they are participants in a study.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We hypothesise that this type of effect may be more visible in the long term. Although we obtained similar results (included in the general health variable) in the clinical trial previously conducted by our team, it lacked a control group [23]. This study confirmed the efficacy of the intervention, since the differences between the two groups are very notable, thus providing evidence that the changes are not due to the mere passage of time or the fact that the patients are being evaluated and know that they are participants in a study.…”
Section: Discussionsupporting
confidence: 66%
“…The brief group intervention protocol for family members (9 h) followed a similar structure to the programme implemented in the previous study [23], and focused on (a) values clarification, (b) defusion strategies, (c) mindfulness training, (d) committed action, and (e) psychological acceptance. The theoretical and clinical skills guide by Harris, Páez, Montesinos, and Valdivia [32][33][34] was used as a basis for the therapeutic techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation